Answer:
B. (1 , 3 )
Explanation:
Step 1 Rearrange.
![x + 3y = 10 \: \: (1) \\ y = x + 2 \: \: \: (2) \\ x + 3y = 10 \: \: (1)\\ x - y = - 2 \: \: \: (2)\\](https://img.qammunity.org/2021/formulas/mathematics/middle-school/pqw2fhi22rbn2d3hrq83v28qatlpjhwb5v.png)
Step 2 : Multiply equation 1 by the coefficient of x in equation 2
Step 2 : Multiply equation 1 by the coefficient of x in equation 2Multiply equation 2 by the coefficient of x in equation 1
Step 3 : Subtract equation 4 from equation 3 and solve for y
![x + 3y = 10 \: \: (3)\\ x - y = - 2 \: \: \: (4) \\ 4y = 12 \\ (4y)/(4) = (12)/(4) \\](https://img.qammunity.org/2021/formulas/mathematics/middle-school/x4ajoit1kf0sge2udm7ua7ipfivwfteipf.png)
Substitute the value for y in to equation 1. or equation 2 and solve for x .
![y = 3 \\substitute \: 3 \: for \: y \: \\ in \: eq \: 1 \: or \: 2 \\ x + 3y = 10 \\ x + 3(3) = 10](https://img.qammunity.org/2021/formulas/mathematics/middle-school/3f087kr6yld985t45hqltqdua4rlxgdwf8.png)
![x + 9 = 10 \\ x = 10 - 9 \\ x = 1 \\ \\ (x \: y) = (1 \: \: 3)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/og8v8zg4tuzypdjywqbmeo25jm75ozvdrx.png)